Sustainable Development as a Wicked Problem: The Case of the Brazilian Amazon Region - Machado, Marcelo; Rocha, Aline; Tartarotti, Natalia (European Journal of Sustainable Development, 2023)
The global importance of the Amazon rainforest is abundantly evident. It is the world’s largest tropical rainforest, home to incredible biodiversity, and arguably an essential part of the earth’s already fragile climate system. Exploiting the Amazon beyond planetary boundaries, in other words, beyond a threshold the forest cannot regenerate itself from, may have catastrophic, global impacts. Conversely, Brazil is an industrialized yet developing country far from realizing its potential to become an economic superpower. To this day, millions of Brazilians still live below the poverty line. Hence, Brazil cannot afford to ignore the economic potential of the Amazon’s vast resources. The issue becomes how to use those resources effectively and efficiently for economic development. The key is perhaps a sustainable development approach. Considering the diversity of internal (i.e., Brazilian) and external (i.e., foreign) stakeholders, there is no agreement of what sustainable development would mean when it comes to the Brazilian Amazon Region (BAR). The challenge is the fact that environmental and social problems are not just complex problems. According to Brown et al (2010), they are very hard to properly define. Buchanan (1992) concluded these types of problems do not fit within any specific subject matter. In this research, we propose the sustainable development of the BAR as a wicked problem (Rittel and Webber, 1973). The main purpose of this study is to conduct an analysis of stakeholders to confirm this hypothesis. This study employs systems thinking, specifically Peter Checkland’s (1989) Soft System Methodology as the conceptual foundation of the analysis of evidence from the field. Preliminary findings are summarized, and conclusions with conceptual and practical considerations are provided. Limitations and opportunities for future studies are also included. Keywords: sustainable development, wicked problems, Brazilian Amazon, system thinking, soft system methodology.